Programmed death‐ligand 1 immunoexpression in matched biopsy and liquid‐based cytology samples of advanced stage non‐small cell lung carcinomas - Deepali Jain; Supraja Sukumar; Anant Mohan; Venkateswaran K. Iyer (2018)
Programmed death-ligand 1 (PD-L1) immunohistochemistry (IHC) is essential in patients of advanced non-small-cell lung cancer to determine eligibility for immunotherapy. PD-L1 IHC assays have been clinically validated only on formalin-fixed paraffin-embedded tissue; however, lung cancer is frequently diagnosed on cytology. PD-L1 immunocytochemistry (ICC) has shown high concordance of immunoexpression between cytology samples and paired small biopsies. Feasibility of liquid-based cytology (LBC) smears for PD-L1 ICC has not been analysed previously.PD-L1 ICC and IHC (clone SP263) were performed on paired LBC smears and small biopsies, respectively, in patients with advanced non-small-cell lung cancer. Cases with fewer than 100 viable tumour cells on LBC smear/biopsy were excluded from analysis. PD-L1 was interpreted positive when 25% or more tumour cells showed membranous and/or cytoplasmic protein expression of any intensity greater than background staining.A total of 26 patients, harbouring adenocarcinomas (50%) and squamous cell carcinomas (50%), had available bronchial brushings/washings processed as LBC smears and concurrently obtained endobronchial biopsies. PD-L1 IHC was interpreted positive in 46% (12/26) biopsies. PD-L1 ICC was interpreted positive in 35% (9/26) LBC smears, all of which were IHC-positive. No IHC-negative case was positive on cytology. The overall concordance between LBC smears and small biopsies was 88.4%.PD-L1 ICC can be performed on LBC processed smears, with certain challenges in interpretation inherent to LBC smears and their processing methods. Nevertheless, they represent a potential resource for ICC, especially when alternate histology material is not available. Future studies are required to validate the predictive value of PD-L1 ICC on LBC smears.